2022
DOI: 10.1108/ijwhm-07-2021-0143
|View full text |Cite
|
Sign up to set email alerts
|

Do broken promises matter? The effects of psychological contract breach on job embeddedness and nurses' work attitudes

Abstract: PurposeThis research investigates the effects of psychological contract breach on the fit, links and sacrifice dimensions of job embeddedness as well as the mediating roles of these three subcomponents in the relationships between psychological contract breach and nurses' work attitudes.Design/methodology/approachData were collected from 591 nurses from private general hospitals in northern Thailand. The hypotheses were tested and analyzed by means of a confirmatory factor analysis, structural equation modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
(230 reference statements)
0
1
0
Order By: Relevance
“…Breach of a relational contract has been found to be associated with job dissatisfaction and increased turnover intent (Hartmann & Rutherford, 2015). Such contract breach may result in a redefinition of the psychological contract to become purely transactional, and previous research among nurses/ health-care workers indicates psychological contract breach to be associated with deteriorated trust, less work engagement and job satisfaction, and an intention to leave (Akkermans, Bal & De Jong, 2019;Dechawatanapaisal, 2022;Trybou, de Pourco, Paeshuyse & Gemmel, 2014). Thompson and Bunderson (2003) suggested that the psychological contract was not solely grounded in a monetary (transactional) or social (relational) exchange but could also be grounded in the employee's ideology concerning the work.…”
Section: Introductionmentioning
confidence: 99%
“…Breach of a relational contract has been found to be associated with job dissatisfaction and increased turnover intent (Hartmann & Rutherford, 2015). Such contract breach may result in a redefinition of the psychological contract to become purely transactional, and previous research among nurses/ health-care workers indicates psychological contract breach to be associated with deteriorated trust, less work engagement and job satisfaction, and an intention to leave (Akkermans, Bal & De Jong, 2019;Dechawatanapaisal, 2022;Trybou, de Pourco, Paeshuyse & Gemmel, 2014). Thompson and Bunderson (2003) suggested that the psychological contract was not solely grounded in a monetary (transactional) or social (relational) exchange but could also be grounded in the employee's ideology concerning the work.…”
Section: Introductionmentioning
confidence: 99%